Productivity Dynamics and Rural Industrialization in India. (January 2020) - Sato, Takahiro; Aggarwal, Aradhna
Since the late 1990s, industrialization in India has been driven by the rural organized manufacturing sector. This paper examines the effects of firms' dynamics on rural industrialization in India, using plant-level panel data, to investigate the characteristics of rural industrialization in India in recent years. In particular, the paper focuses on productivity differences among continuing, entering, and exiting firms. The results show that both labour and total factor productivity of the organized manufacturing sector in rural areas increased during 2000–2006 and the aggregate productivity growth is supported by the productivity growth of the continuing firms, the entry of productive firms, and the exit of less-productive firms. The paper can conclude that firms' productivity dynamics contributed to the current rural industrialization in India. JEL: O14, O47, O53